Non-apoptotic functions of apoptosis-regulatory proteins - Galluzzi, Lorenzo; Kepp, Oliver; Trojel-Hansen, Christina; Kroemer, Guido (EMBO reports, 2012)
During the past two decades, apoptotic cell death has been the subject of an intense wave of investigation, leading to the discovery of multiple gene products that govern both its induction and execution. In parallel, it has progressively become evident that most, if not all, proteins that had initially been discovered for their essential role in apoptosis also mediate a wide range of non‐apoptotic functions. On the one hand, apoptotic regulators and executioners are involved in non‐lethal physiological processes as diverse as cell cycle progression, differentiation, metabolism, autophagy and inflammation. On the other hand, pro‐apoptotic proteins can control other modalities of programmed cell death, in particular regulated necrosis. In this review, we summarize the unconventional roles of the apoptotic core machinery from a functional perspective and discuss their pathophysiological implications. EMBO reports advance online publication 9 March 2012; doi:10.1038/embor.2012.19 Galluzzi, Kroemer and colleagues summarize the important roles of apoptotic regulators and executioners in non‐lethal physiological processes as diverse as cell cycle progression, differentiation, metabolism, autophagy and inflammation.